2016
DOI: 10.1128/jcm.02784-15
|View full text |Cite
|
Sign up to set email alerts
|

Towards Development of Improved Serodiagnostics for Tularemia by Use of Francisella tularensis Proteome Microarrays

Abstract: e Tularemia in humans is caused mainly by two subspecies of the Gram-negative facultative anaerobe Francisella tularensis: F. tularensis subsp. tularensis (type A) and F. tularensis subsp. holarctica (type B). The current serological test for tularemia is based on agglutination of whole organisms, and the reactive antigens are not well understood. Previously, we profiled the antibody responses in type A and B tularemia cases in the United States using a proteome microarray of 1,741 different proteins derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
10
0
2
Order By: Relevance
“…Immunogenic protein antigens FTT1269, FTT1329, FTT1483 ( Francisella tularensis ), WR148, WR101 ( Vaccinia virus ), BB_B19, BB_O34 ( Borrelia burgdorferi ), Rv3362 ( Mycobacterium tuberculosis ), and OTB1104 ( Orientia tsutsugamushi ) were purified as previously described 26 . Briefly, Protein-encoding T7-expression plasmids were used for protein expression in E. coli cells in vivo .…”
Section: Methodsmentioning
confidence: 99%
“…Immunogenic protein antigens FTT1269, FTT1329, FTT1483 ( Francisella tularensis ), WR148, WR101 ( Vaccinia virus ), BB_B19, BB_O34 ( Borrelia burgdorferi ), Rv3362 ( Mycobacterium tuberculosis ), and OTB1104 ( Orientia tsutsugamushi ) were purified as previously described 26 . Briefly, Protein-encoding T7-expression plasmids were used for protein expression in E. coli cells in vivo .…”
Section: Methodsmentioning
confidence: 99%
“…The immunoblotting technique has also been used to determine the F. tularensis immunoreactive proteins using sera from infected or vaccinated persons (Havlasováet al, 2002;Eyles et al, 2007;Sundaresh et al, 2007;Nakajima et al, 2016). These studies have shown that the most immunoreactive F. tularensis included the chaperone proteins dnaK and groEL, two chaperonins (10 and 60 kDa), the elongation factor EF-Ts, membrane proteins (23 kDa hypothetical protein, 17 kDa TUL4 protein, OmpH and FopA), enzymes (pyruvate dehydrogenase, acetyl-CoA carboxylase, pyrrolidone-carboxylate peptidase, isocitrate dehydrogenase, glutamine synthetase, etc.)…”
Section: Immunoblotsmentioning
confidence: 99%
“…This difference may reflect the higher specificity of the immunoblot technique but also low sensitivity of this method in patients with low antibody titers. Several studies have tried to dissect the immune response of patients infected with F. tularensis to develop more sensitive and specific serological tests (Havlasovaé t al., 2002;Eyles et al, 2007;Sundaresh et al, 2007;Nakajima et al, 2016). Although these studies have well defined the most immunodominant F. tularensis antigens, they have not given rise to the development of new serological tests with improved performances compared to those currently used for tularemia diagnosis.…”
Section: Commentsmentioning
confidence: 99%
“…El estudio e identificación de los diferentes antígenos de membrana permitirá confirmar cuales son los antígenos inmunodominantes de Francisella tularensis y su importancia inmunopatogénica y protectora 3,24,25 .…”
Section: Estructura Antigénica Y Factores De Virulenciaunclassified
“…En lo que respecta a las reacciones cruzadas con otras enfermedades, los estudios llevados a cabo en Castilla y León no encontraron relación con Yersinia enterocolitica ni con Proteus OX19 155,176 , aunque otros autores 25,177 han descrito casos de reacciones cruzadas con los antígenos de estas bacterias.…”
Section: Reacciones Cruzadasunclassified